Moringa agroindustry infrastructure development in Pilangrejo Village - Muhammad Yusuf Rafif; Aufi Fauziyah Dlilah HFB; Muhajir Muhajir; Rival Effendi; Rizky Rayhan Najib Soamangon (Universitas Muhammadiyah Magelang, 2022)
Moringa is a type of herbaceous plant that has many benefits and contains high nutrition. One of the products that can be produced is moringa powder. To produce high quality moringa powder, standardized processing methods are needed starting from the production infrastructure to the processing techniques. However, this industry stopped operating due to inadequate production facilities and infrastructure and human resources. Therefore, through the The Program Holistik Pembangunan dan Pemberdayaan Desa (PHP2D) activities are carried out to empower partners in processing Moringa leaves. The implementation method applied is socialization, training, production house revitalization and practice accompanied by assistance. The results obtained are that production facilities are in accordance with standards and interest in production has increased, supported by skills in using good production facilities.